INCREASING STUDENTS’ VOCABULARY BY USING MIND MAPPING TECHNIQUE AT SMP N 2 BITUNG - Tara A. Delatu; Diane Wowor; Sarah Kamagi (Journal of English Culture, Language, Literature and Education, 2020)
The purpose of the study was to find out whether using mind mapping technique can increase students' vocabulary or not. It was conducted at SMP N 2 Bitung. The subject in this study was Class V11-4, academic year 2017/2018, which consisted of 35 students. This research was a pre-experimental design with one group pre-test-post-test. Pre-test is the test which was given to the students before treatment to find out students' vocabulary stock. Post-test is the test which was given to the students to find out the students' achievement after treatment or teaching them by using mind mapping technique. The findings showed that the students' score in post-test were higher than the pre-test. The result of the data analysis revealed that the mean score of post-test (82) was higher than the pre-test (49). In addition the standard deviation of pre-test was slightly higher (7.05) than the standard deviation of post-test (5.71). This indicated that the use of mind mapping technique increased students' vocabulary.